A profile of the Tarlac College of Technology faculty implications for faculty development - Donato, Catalina R. 1911- (s.n.], 1973)
The faculty members from 1965 to 1972 of whom there are slightly more males than females are middle-aged, married, and have 16-20 years of teaching experience. The typical faculty member teaches 15 to 18 hours in his own major or minor field, renders community service in home beautification, improving nutritional practices, helping parents rear children, and helping plan leisure time, activities and hobbies.